PENGARUH PENGGUNAAN MEDIA POSTER TERHADAP KEMAMPUAN MENULIS PETUNJUK SISWA DI KELAS III UPTD SPF SD INPRES MACCINI SOMBALA 1 KOTA MAKASSAR - Ayunia Putri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The instruction writing skills of third-grade students at the UPTD SPF SD Inpres Maccini Sombala 1 are still low; students often have difficulty expressing ideas and arranging words, making learning boring. This study offers poster media as an alternative to motivate and facilitate more structured instruction writing. The purpose of the study was to analyze the effect of poster media use on students' instruction writing skills. The study used a quasi-experimental design with a one-group pretest– posttest on 39 third-grade students in the 2024/2025 academic year. Data were collected through pretests and posttests, then analyzed descriptively and inferentially using Paired Sample t-Tests. The results showed a significant improvement in writing skills after the implementation of poster media. The average score increased from 44.10 (pretest) to 87.17 (posttest), with a change in the distribution of value categories from predominantly low/moderate to predominantly high–very high. The paired t-test produced a p-value <0.001, rejecting H0 and confirming that poster media had a significant effect on improving instruction writing skills in Indonesian subjects. These findings recommend poster media as an effective learning strategy to build motivation, clarify procedural steps, and improve the learning outcomes of elementary school students.